Are green universities producing greener future leaders? - Mohd Ghaus, Raihana; Harun, Rosta; Lim, Kuang Hock; Ponrahono, Zakiah (Malaysian Institute of Planners, 2017)
In recent years, studies on campus sustainability have been conducted to measure the impact that universities have on the environment and several mechanisms to measure and rank universities globally on how they perform in sustainability have been proposed. The UI Greenmetrics ranks universities based on sustainable performance ratings and focused more on the initiatives and opportunities provided to achieve sustainability but did not address the issue of environmental literacy among the university students. This study aims to understand how sustainable practices and policies adopted by Green Universities as well as demographic factors relate to the level of environmental attitude and responsible environmental behaviour of Malaysian student leaders. A census survey was carried out on student leaders of Malaysian public universities to assess their level of perception, attitude, personal responsible environmental behaviour (REB) and REB with regards to UI Greenmetrics Criteria. The Mann-Whitney U test conducted revealed that there was no significant difference in the level of the assessed components across all demographic factors between green and nongreen universities. Spearman rank order correlation showed that there was a significant positive correlation between perception and personal REB (rs(322) = .385, p < .05) as well student council REB (rs(322) = .542, p < .05). Attitude was found to have a significant negative correlation with student council REB (rs(322) = -.114, p < .05) while a high level of personal REB was significantly correlated with student council behaviour (rs(322) = .579, p < .05).